Diary Of A Wimpy Kid : Do - It - Yourself Book - Kinney, Jeff (London Puffin, 2011)
A Wimpy Kid diary. It lets you draw your own Wimpy-Kid-style cartoons, fill in facts and lists, check out the full-colour comics inside and even write your own Wimpy Kid journal
Check the BOOK when Returns
Keywords: Children's Literature - Fiction : Humorous